Are there differences in the kinetic parameters of the vertical jump performed by beach volleyball players on different types of sand? - Neto, F. O.; Silva, G: M.; Simim, M. A. M.; Banja, T.; Sousa, F.; Fonseca, P.; Goethel, M.; Romero, R.; de Jesus, K.; Medeiros, A. I. A. (Sports Biomechanics, 2024)
Beach volleyball (BV) is an intermittent sport characterised by short-duration and highly demanding activities with low intensity periods. Establishing if players` jump ability is influenced by sand granulometry is a useful information for sport scientists, coaches and players. This study aimed to assess the possible differences in the kinetics parameters of the vertical jump on different types of sand performed by BV players. Twelve elite female players performed six countermovement jumps (CMJs) in three different surface conditions (fine sand, reference, coarse sand) in a random counterbalanced order (216 jumps). A generalised mixed model approach detected differences for CMJ model in total duration (p: 0.016), eccentric phase duration (p: 0.007), concentric phase duration (p: 0.011), time to peak power (p: < 0.001), time to peak force (p: 0.014), maximum rate force development concentric phase (p: 0.004), maximum velocity (p: 0.028) and peak power eccentric (p: 0.018). Coarse sand decreases the time spent jumping compared to fine sand, without a penalty to jump height. Coaches and athletes should take this information into account to enhance their understanding of practice strategies and game conditions. One might anticipate a faster pace in games played on coarse sand and a slower pace on fine sand.